2005
DOI: 10.1093/jn/135.10.2291
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Dietary Polyphenols

Abstract: Dietary polyphenols have been shown to possess cardioprotective effects. For example, the most noted role of grape polyphenols is in the French Paradox, in which a diet high in saturated fat accompanied by regular consumption of red wine is associated with a low risk of coronary heart disease (CHD). Initially, the paradox was thought to be driven by the postulated major action of grape polyphenols in inhibiting LDL oxidation. Although many studies have shown inhibitory effects of polyphenols on LDL oxidation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
0
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(219 citation statements)
references
References 31 publications
6
180
0
15
Order By: Relevance
“…The mechanism of action for the beneficial effects of polyphenols on CVD was previously thought to be associated with their antioxidant activity (23) . However, many polyphenols are metabolised in the body and these metabolites have much lower antioxidant capacities than their parent compounds, suggesting that antioxidant activity may not be their only mechanism of action (12) .…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…The mechanism of action for the beneficial effects of polyphenols on CVD was previously thought to be associated with their antioxidant activity (23) . However, many polyphenols are metabolised in the body and these metabolites have much lower antioxidant capacities than their parent compounds, suggesting that antioxidant activity may not be their only mechanism of action (12) .…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…The metabolic consequences of elevated plasma enterolactone and enterodiol concentrations have not been elucidated, and more evidence from human studies is required to confirm whether these molecules are involved in reducing CVD risk and to elucidate their mechanisms of action. It is possible that the lignans may possess similar cardioprotective effects to those reported for other polyphenolic compounds, including reducing LDL-cholesterol oxidation, changes in cholesterol synthesis and re-cycling, and changes in the metabolism of triacylglycerols (Zern & Fernandez, 2005), although as yet there is limited evidence to support these hypotheses. Men from the Kuopio Ischaemic Heart Disease Risk Factor Study in the highest quartile of serum enterolactone concentrations were found to have a 65 % lower risk of acute coronary events than men from the lowest quartile (Vanharanta et al 1999).…”
Section: Mammalian Lignans and Whole Grainsmentioning
confidence: 99%
“…quercetin, myricetin and kaempferol) [22]. The relatively high concentrations of resveratrol (and likely other polyphenols) in red wine is thought to be the explanation for the so-called "French-paradox" [23,24].…”
Section: Resveratrol: Synthesis Sourcesmentioning
confidence: 99%